A Survey of The Unoccupied Acoustic Conditions of Active Learning Classrooms in Montreal - Hadavi, Shiva; Lee, Joonhee (Canadian Acoustics, 2019)
Educators have developed innovative teaching strategies in order to maximize learning outcomes in classrooms. Active learning classrooms are new learning spaces that facilitate the teaching strategies with enhanced students’ engagement and collaborative discussions. However, acoustic requirements of the active learning classrooms have not been investigated yet. This paper presents, thus, the acoustic conditions of the active learning classrooms located in Montreal. The acoustical parameters such as background noise, reverberation time and speech transmission index in unoccupied conditions are examined. The results show that although all the classes are newly renovated and equipped to be used as active learning classrooms, the majority of them do not meet the standard acoustic requirements for reverberation time and background noise level respectively. Further studies on occupied conditions of active learning classrooms can provide a better understanding of the acoustical design requirements for these spaces.